Customer incivility and service sabotage in the hotel industry. Issue 5 (16th April 2020) - Cheng, Bao; Guo, Gongxing; Tian, Jian; Shaalan, Ahmed
Abstract : Purpose: Using equity theory, this study aims to examine the role of customer incivility in effecting service sabotage among hotel employees by recognizing the mediating role of revenge motivation and the moderating effect of emotion regulation. Design/methodology/approach: A multi-wave, multi-source questionnaire survey was conducted with 291 employee–supervisor dyads at chain hotels in Shenzhen, China. Previously developed and validated measures for customer incivility, revenge motivation, emotion regulation and service sabotage were adopted to test the hypotheses. Findings: Customer incivility increased employees' revenge motivation and service sabotage. Emotion regulation acted as a boundary condition for customer incivility's direct effect on revenge motivation and its indirect effect on service sabotage through revenge motivation. Cognitive reappraisal mitigated the detrimental influence of customer incivility, whereas expressive suppression worsened its adverse effects. Practical implications: Managers should monitor and deter the emergence of uncivil behaviors, provide psychological support for employees experiencing customer incivility and encourage these employees to use cognitive reappraisal rather than expressive suppression as an emotion regulation strategy. Originality/value: To the authors' knowledge, no prior research has investigated the customer incivility–service sabotage relationship in the hotel industry. This study sheds light on how customer incivility can motivate service sabotage among hotel employees. Furthermore, the authors used equity theory rather than the commonly adopted resources perspective to offer new insights into the customer incivility–service sabotage relationship.